Hepatoprotective activity evaluation of DLBS1433 bioactive fraction from phaleria macrocarpa - FLORENSIA NAILUFAR; HERY KRISTIANA; RAYMOND R. TJANDRAWINATA (International Journal of Pharma and Bio Sciences, 2017)
Phaleria macrocarpa is an Indonesian medicinal plant which has been known for its various uses. The present study aims to evaluate efficacy, antioxidant activity and cytotoxicity of DLBS1433, a bioactive fraction obtained from P. macrocarpa, as a hepatoprotective agent in ethanol-induced liver damage in Rattus norvegicus. Ethanol was administered to all rats (5 g/kg/day, 20% v/v) for 4 w and followed by treatment with DLBS1433-60 and DLBS1433-90 for 1 w, respectively. Curcuma domestica extract treatment group was used as a comparison. Blood biochemical parameters, which are the markers of liver function including alanine transaminase (ALT), aspartate transaminase (AST), total bilirubin and gamma-glutamyl transferase (GGT), were examined to determine the hepatoprotective effect of DLBS1433. Liver histopathology examination was also conducted in this study. Ethanol administration for 4 w was able to increase blood biochemical parameters which are the markers of liver function. Ethanol administration followed by DLBS1433-60 treatment showed lower blood biochemical parameters and better liver histopathology results compared to DLBS1433-90 treatment group. Based on the results of the present study, it can be concluded that DLBS1433-60 was considered as a potential hepatoprotective agent as shown by the results of blood biochemical parameters and liver histopathological examination.